The Effect of Final PPH Rate Reduction on Taxpayer Compliance of Micro, Small and Medium Enterprises (MSMEs) with Tax Sanctions as a Mediation Variable (Case Study on Batik MSME in Jambi Province) - Thamrin, Wisnami Syakhira; Tiswiyanti, Wiwik; Friyani, Rita (East Asian Journal of Multidisciplinary Research, 2024)
The aim of this research is to ascertain, as an intervening variable, how the decrease in PPh rates affects MSMEs' compliance with tax sanctions. MSME batik actors in the Jambi Region constituted the study's sample. The research sample was 97 MSME batik taken using the purposive sampling method. Data were collected through questionnaires and observations. The mentioned study is a quantitative study using primary data, to test the relationship between factors through the SmartPLS 4.1.0.6 application. The results showed that the reduction in UMP rates had a significant effect on the relationship between MSME compliance, the reduction in UMP rates had a significant negative effect on the relationship between tax sanctions. Tax sanctions had no appreciable beneficial impact on MSME compliance. Tax sanctions did not affect the correlation between the reduction in UMP rates and MSME compliance.